A fungus (Trametes pubescens) resists cadmium toxicity by rewiring nitrogen metabolism and enhancing energy metabolism - Liu, Jing; Fu, Pengcheng; Wang, Li; Lin, Xiuying; Enayatizamir, Naeimeh (Frontiers in Microbiology, 2022)
As a primary goal, cadmium (Cd) is a heavy metal pollutant that is readily adsorbed and retained in rice, and it becomes a serious threat to food safety and human health. Fungi have attracted interest for their ability to remove heavy metals from the environment, although the underlying mechanisms of how fungi defend against Cd toxicity are still unclear. In this study, a Cd-resistant fungus Trametes pubescens (T. pubescens) was investigated. Pot experiments of rice seedlings colonized with T. pubescens showed that their coculture could significantly enhance rice seedling growth and reduce Cd accumulation in rice tissues. Furthermore, integrated transcriptomic and metabolomic analyses were used to explore how T. pubescens would reprogram its metabolic network against reactive oxygen species (ROS) caused by Cd toxicity. Based on multi-omic data mining results, we postulated that under Cd stress, T. pubescens was able to upregulate both the mitogen-activated protein kinase (MAPK) and phosphatidylinositol signaling pathways, which enhanced the nitrogen flow from amino acids metabolism through glutaminolysis to α-ketoglutarate (α-KG), one of the entering points of tricarboxylic acid (TCA) cycle within mitochondria; it thus increased the production of energy equivalents, adenosine triphosphate (ATP) and reduced nicotinamide adenine dinucleotide phosphate (NADPH) for T. pubescens to resist oxidative damage. This study can enable a better understanding of the metabolic rewiring of T. pubescens under Cd stress, and it can also provide a promising potential to prevent the rice paddy fields from Cd toxicity and enhance food safety.